Influence of Different Patellofemoral Design Variations Based on Genesis II Total Knee Endoprosthesis on Patellofemoral Pressure and Kinematics. (31st January 2017) - Leichtle, Ulf G.; Lange, Barbara; Herzog, Yvonne; Schnauffer, Peter; Leichtle, Carmen I.; Wülker, Nikolaus; Lorenz, Andrea
Abstract : In total knee arthroplasty (TKA), patellofemoral groove design varies greatly and likely has a distinct influence on patellofemoral biomechanics. To analyse the selective influence, five patellofemoral design variations were developed based on Genesis II total knee endoprosthesis (original design, being completely flat, being laterally elevated, being medially elevated, and both sides elevated) and made from polyamide using rapid prototyping. Muscle-loaded knee flexion was simulated on 10 human knee specimens using a custom-made knee simulator, measuring the patellofemoral pressure distribution and tibiofemoral and patellofemoral kinematics. The measurements were carried out in the native knee as well as after TKA with the 5 design prototypes. The overall influence of the different designs on the patellofemoral kinematics was small, but we found detectable effects for mediolateral tilt (p < 0.05 for 35°–80° flexion) and translation of the patella (p < 0.045 for 20°–65° and 75°–90°), especially for the completely flat design. Considering patellofemoral pressures, major interindividual differences were seen between the designs, which, on average, largely cancelled each other out. These results suggest that the elevation of the lateral margin of the patellofemoral groove is essential for providing mediolateral guidance, but smooth contouring as with original Genesis II design seems to be sufficient. The pronounced interindividual differences identify a need for more patellofemoral design options in TKA.